1997
DOI: 10.1021/tx9601519
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Covalently Bound Form of Microcystin-LR in Salmon Liver and Dungeness Crab Larvae

Abstract: The chemically unique nature of the C20 beta-amino acid (2S,3S,8S,9S)-3-amino-9-methoxy-2,6,8-trimethyl-10-phenyldeca-4,6- dienoic acid (Adda) portion of the microcystins has been exploited to develop a strategy to analyze for the total microcystin-LR (1; see Figure 1) burden in salmon liver and crab larvae tissues. Lemieux oxidation of microcystin-LR (1) gives 2-methyl-3-methoxy-4-phenylbutanoic acid (2), a unique marker for the presence of microcystins. The butanoic acid 2 can be isolated and detected by GC/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
69
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(83 citation statements)
references
References 41 publications
13
69
1
Order By: Relevance
“…These results suggest that lower amounts of permanganate are insufficient to generate MMPB from cyanobacterial samples; therefore, oxidization of cyanobacterial samples with a high dose of permanganate in the reaction solution should be considered. These findings differ from those of previous studies, which have usually been conducted using lower concentrations of permanganate [38][39][40][41][42][43][44][45][46][47].…”
Section: Effect Of the Concentration Of Permanganate On The Yield Andcontrasting
confidence: 99%
See 2 more Smart Citations
“…These results suggest that lower amounts of permanganate are insufficient to generate MMPB from cyanobacterial samples; therefore, oxidization of cyanobacterial samples with a high dose of permanganate in the reaction solution should be considered. These findings differ from those of previous studies, which have usually been conducted using lower concentrations of permanganate [38][39][40][41][42][43][44][45][46][47].…”
Section: Effect Of the Concentration Of Permanganate On The Yield Andcontrasting
confidence: 99%
“…The results revealed that the yields of MMPB under neutral or alkaline conditions were higher than those under acidic conditions, with the highest concentration being produced under weak alkaline conditions (pH ∼9). These results are consistent with those of previous studies in which the pH of the solution was adjusted to approximately 9 using potassium bicarbonate to produce MMPB in oxidation reactions [38][39][40][41][42][43][44][45][46][47]. Among the five pH values evaluated, the resulting MMPB concentrations were shown to have only minor differences after 1 h, indicating that MMPB was stable under different pH conditions.…”
Section: Effect Of Ph On the Yield And Stability Of Mmpbsupporting
confidence: 90%
See 1 more Smart Citation
“…To date, only Tsuji et al [15] have applied this MMPB method for total MCs detection in lake sediments; however, there still exists a problem in that the necessary very-low reaction temperature is difficult to achieve as it involves oxidation of the MCs to form MMPB by ozonolysis. Several studies have reported that oxidizing the toxins by Lemieux oxidation is a more sensitive analytical method for total MC detection, and this technique has been widely applied in a range of sample matrices, including cyanobacteria [19,20], or animal tissues [21][22][23][24][25][26]. Unfortunately, there is still little information available regarding the effects of the primary factors such as the reaction conditions and sediment characteristics (i.e., organic matter) on the oxidation efficiency, and application of the MMPB method using Lemieux oxidation to the analysis of lake sediment has still not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Microcystins can be accumulated in the tissues of fish (Tencalla et al, 1994;Soares et al, 2004), mussels (Amorim and Vasconcelos, 1999;Vasconcelos, 1995;Williams et al, 1997b;Dionisio Pires et al, 2004) and aquatic macrophytes (Pflugmacher et al, 1998) and also transferred from crab larva to salmons through food chain (Williams et al, 1997a). Many fishes are not able to avoid the ingestion of these toxic organisms through food in the waters such as small eutrophicated lakes and aquaculture ponds (Tencalla and Dietrich, 1997;Magalhães et al, 2001).…”
Section: Introductionmentioning
confidence: 99%